Bioenergetic Mechanisms Linking V˙O2 Kinetics and Exercise Tolerance. Issue 4 (October 2021) - Goulding, Richie P.; Rossiter, Harry B.; Marwood, Simon; Ferguson, Carrie
Abstract : We hypothesize that the V˙O2 time constant (τV˙O2 ) determines exercise tolerance by defining the power output associated with a "critical threshold" of intramuscular metabolite accumulation ( e.g., inorganic phosphate), above which muscle fatigue and work inefficiency are apparent. Thereafter, the V˙O2 "slow component" and its consequences (increased pulmonary, circulatory, and neuromuscular demands) determine performance limits. Abstract : V˙O2 kinetics determine exercise tolerance by mediating the power output at which muscle metabolite accumulation exceeds a "critical threshold."